PENGARUH PENAMBAHAN TEPUNG DAUN KELOR (Moringa Oleifera) TERHADAP ORGANOLEPTIK NUGGET DAGING ITIK AFKIR - Murlan, Welsis; Komala, Refika; Elisia, Rini; Yontoni, Mai (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2025)
This research aims to determine the effect of adding moringa leaf flour on the organoleptic properties of spent duck nuggets. Nuggets are one of the food products favored by various segments of society due to their ease of preparation and delicious taste. Duck meat is one of the animal protein sources that is widely utilized in different food preparations. Moringa (Moringa oleifera) is a plant often used as a fence plant by the community; the moringa plant also has various benefits. However, culled duck meat is often considered a low-value product and tends to be neglected. To increase the added value of culled duck meat, moringa leaf powder is added to produce nuggets. This study uses an experimental method with a Completely Randomized Design (CRD) with 4 treatments and 25 panelists as repetitions with varying amounts of moringa leaf flour. (0g, 5g, 10g, 15g). Organoleptic data testing using the SPSS 16 for Windows program. Statistical analysis was used to determine the effect of the treatment, specifically the non-parametric Kruskal-Wallis analysis. The research results showed that the addition of moringa leaf powder (Moringa oleifera) to duck nuggets with treatments of 5 grams to 15 grams had a significant effect (P<0.05) on color, texture, aroma, and taste.